2021
DOI: 10.3390/molecules26051476
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of Taxifolin on ZEB2 Cancer Signaling in HepG2 Cells

Abstract: Polyphenols, secondary metabolites of plants, exhibit different anti-cancer and cytoprotective properties such as anti-radical, anti-angiogenic, anti-inflammation, or cardioprotective. Some of these activities could be linked to modulation of miRNAs expression. MiRNAs play an important role in posttranscriptional regulation of their target genes that could be important within cell signalling or preservation of cell homeostasis, e.g., cell survival/apoptosis. We evaluated the influence of a non-toxic concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The inhibition of AKT phosphorylation by taxifolin counteracted possible EMT effects originated from ZEB2 upregulation. 151 In hepatocellular carcinoma cells, Huh7 cells, upstream phosphorylated AKT and GSK-3β were downregulated in puerarin-treated cells. 152 Lung cancer: the levels of p-AKT and p-GSK-3β, but had no significant effect on ERK phosphorylation.…”
Section: Flavonoids and The Pi3k/akt/mtor Signaling Pathwaymentioning
confidence: 93%
See 2 more Smart Citations
“…The inhibition of AKT phosphorylation by taxifolin counteracted possible EMT effects originated from ZEB2 upregulation. 151 In hepatocellular carcinoma cells, Huh7 cells, upstream phosphorylated AKT and GSK-3β were downregulated in puerarin-treated cells. 152 Lung cancer: the levels of p-AKT and p-GSK-3β, but had no significant effect on ERK phosphorylation.…”
Section: Flavonoids and The Pi3k/akt/mtor Signaling Pathwaymentioning
confidence: 93%
“…137 Also in HepG2 cells, taxifolin inhibited AKT phosphorylation, the latter being a decisive signal for vimentin downregulation. 151 To confirm this hypothesis, it was found that the AKT inhibitor GSK690693 showed correlation between AKT activity and vimentin expression.…”
Section: Flavonoids and The Pi3k/akt/mtor Signaling Pathwaymentioning
confidence: 96%
See 1 more Smart Citation
“…27 Taxifolin has been shown to possess anticancer properties by diminishing ZEB signaling through AKT. 28 It has also been shown that taxifolin treatment can significantly attenuate rotenone-induced renal dysfunction. 29…”
Section: Introductionmentioning
confidence: 99%
“…27 Taxifolin has been shown to possess anticancer properties by diminishing ZEB signaling through AKT. 28 It has also been shown that taxifolin treatment can significantly attenuate rotenone-induced renal dysfunction. 29 The combination of different drugs could reduce ototoxic side effects without the cost of developing a new antibiotic or compromising antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%